Synthesis of oxime from a renewable resource for metal extraction - Hoang, A.; Tran, T.; Nguyen, H.; Vu, H.; Vo, T.; Phan, Chi; Nguyen, Thanh Vinh (Springer, 2015)
A new method for semi-synthesis of alkyl salicylaldoximes from cardanol is reported. Cardanol was extracted from decarboxylation process of cashew nutshell liquid, an abundant agricultural by-product. Molecular structures, physical and chemical properties of cardanol and oxime derivatives were confirmed by spectroscopic analyses. The produced oximes were successfully employed to extract copper(II) cation from aqueous copper salt solutions, offering a practical and economical pathway to effectively recover metals using agricultural by-products.